PENINGKATAN LAYANAN NASABAH MELALUI PEMANFAATAN TEKNOLOGI INFORMASI DAN APLIKASI DIGITAL PT AGRODANA FUTURES - Athaya, Muhammad Fayi Raihan; Mawardi, Alfiandi Imam (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The use of digital applications to support customer service has become an essential need for companies in the futures trading sector. Fast and accurate market information is crucial to service quality and client decision-making. PT Agrodana Futures utilizes a digital application to efficiently deliver daily updates such as fundamental news and buy/sell recommendations. Kurniawan (2019) states that integrated digital services can improve service efficiency by accelerating the distribution of information to customers. This is supported by Ramadhan (2020), who explains that technology-based applications can create interactive relationships between companies and clients, leading to higher customer satisfaction. This study employed observation and hands-on practice during an internship at PT Agrodana Futures. Findings show that the use of digital applications contributes to improving the effectiveness of customer service, particularly in terms of information speed and clarity. The application serves as the main medium for delivering market information required by clients to make investment decisions. These findings support Wulandari (2021), who noted that digitalization in financial services accelerates data-driven service transformation, and align with Anjani (2018), who stated that information technology can serve as a real-time communication and service enhancement tool for businesses.